The Role of Southeast Asia in The Global Economy: Analysis of The Economic Performance of ASEAN Countries - Nurul Hidayah Siregar; Uci Ningsih; Indhira Resky Imandari (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
This study aims to analyze the strategic role of ASEAN (Association of Southeast Asian Nations) in the global economy through a review of macroeconomic indicators such as Gross Domestic Product (GDP) growth, international trade, foreign direct investment (FDI), and the level of regional economic integration. With a population of over 680 million people and increasingly close economic integration, ASEAN has become one of the largest economic blocs in the world. The method used is a literature review by examining various academic literature, scientific journals, official reports, and publications of relevant international institutions. The results of the study indicate that ASEAN has stable and sustainable economic growth, supported by free trade policies, increasing investment flows, and growing industrial competitiveness, where agreements such as the ASEAN Free Trade Area (AFTA) and the Regional Comprehensive Economic Partnership (RCEP) play a significant role in strengthening market connectivity. However, the study also found challenges in the form of economic disparities between member countries, dependence on specific export sectors, and uneven regulatory and infrastructure barriers. With a strategy of economic diversification, increased infrastructure investment, and the development of the digital sector and innovation-based industries, ASEAN has great potential to strengthen its position as a significant actor in the global economy in the future.